A fluorine-18 labeled radiotracer for PET imaging of γ-glutamyltranspeptidase in living subjects. Issue 31 (24th May 2021) - Gao, Dingyao; Miao, Yinxing; Ye, Siqin; Lu, Chunmei; Lv, Gaochao; Li, Ke; Yu, Chunjing; Lin, Jianguo; Qiu, Ling
Abstract : A radiotracer ([ 18 F]GCPA)2 for sensitively and specifically detecting the expression level of γ-glutamyltranspeptidase in living subjects was reported. Abstract : The expression level of γ-glutamyltranspeptidase (GGT) in some malignant tumors is often abnormally high, while its expression is low in normal tissues. Therefore, GGT is considered as a key biomarker for cancer diagnosis. Several GGT-targeting fluorescence probes have been designed and prepared, but their clinical applications are limited due to their shallow tissue penetration. Considering the advantages of positron emission tomography (PET) such as high sensitivity and deep tissue penetration, we designed a novel PET imaging probe for targeted monitoring of the expression of GGT in living subjects, ([ 18 F]γ-Glu-Cys-PPG(CBT)-AmBF3 )2, hereinafter referred to as ([ 18 F]GCPA)2 . The non-radioactive probe (GCPA)2 was synthesized successfully and [ 18 F]fluorinated rapidly via the isotope exchange method. The radiotracer ([ 18 F]GCPA)2 could be obtained within 0.5 h with the radiochemical purity over 98% and the molar activity of 10.64 ± 0.89 GBq μmol −1 . It showed significant difference in cellular uptake between GGT-positive HCT116 cells and GGT-negative L929 cells (2.90 ± 0.12% vs. 1.44 ± 0.15% at 4 h, respectively). In vivo PET imaging showed that ([ 18 F]GCPA)2 could quickly reach the maximum uptake in tumor (4.66 ± 0.79% ID g −1 ) within 5 min and the tumor-to-muscle uptake ratio was higher than 2.25 ± 0.08 within 30 min. Moreover, the maximum tumor uptake of the control group co-injected with the non-radioactive probe (GCPA)2 or pre-treated with the inhibitor GGsTop decreased to 3.29 ± 0.24% ID g −1 and 2.78 ± 0.32% ID g −1 at 10 min, respectively. In vitro and in vivo results demonstrate that ([ 18 F]GCPA)2 is a potential PET probe for sensitively and specifically detecting the expression level of GGT.